GE_GERICHTE P/24517/2020 vom 3. März 2022 - GE Cour de justice (2022)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;POLICE;ABUS D'AUTORITÉ;CONTRAINTE(DROIT PÉNAL);RECONSIDÉRATION;DROIT D'OBTENIR UNE DÉCISION | CPP.310; CP.312; CP.181; CPP.396.al2